Protective role of propolis in chlorpyrifos-induced changes in the haematological parameters and the oxidative/antioxidative status of Cyprinus carpio carpio - Yonar, M. Enis; Yonar, Serpil Mise; Ural, Mevlut Sener; Silici, Sibel; Dusukcan, Mustafa (Pergamon-Elsevier Science Ltd, 2012)
The protective effect of propolis on haematological parameters and antioxidant status were evaluated in the blood and various tissues of carp exposed to chlorpyrifos (CPF). The fish were exposed to sublethal concentrations of CPF (0.040 and 0.080 mg/L) for 10 days, and propolis (10 mg per kg of fish weight) was simultaneously administered. Samples of the blood and tissue (liver, kidney, and gill) were collected at the end of the experiment and analysed for their oxidant-antioxidant status, including the malondialdehyde (MDA) levels, and the superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activity. The samples were also measured for changes in the haematological parameters, such as the red blood cell (RBC) and white blood cell (WBC) counts, the haemoglobin concentration (Hb), the haematocrit (Ht) level, and the erythrocyte indices: the mean corpuscular volume (MCV), the mean corpuscular haemoglobin (MCH) and the mean corpuscular haemoglobin concentration (MCHC). The findings of this study demonstrated that CPF had a negative effect on the haematological parameters and the antioxidant enzyme activities of the fish; this toxic effect was neutralised by the administration of propolis. The present results suggest that propolis can be effective in the protection of CPF-induced toxicity in fish. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Pesticides; Chlorpyrifos; Propolis; Haematology; Oxidative stress; Fish